The slope of the VO2 slow component is associated with exercise intolerance during severe-intensity exercise - Barbosa, L. F. [UNESP]; Greco, C. C. [UNESP]; Denadai, B. S. [UNESP] (Akademiai Kiado Rt, 2014)
The aim of this study was to analyze the relationship between the slope of the VO2 slow component (VO(2)sc) and exercise tolerance (tlim) during constant-work-rate (CWR) exercise performed within the severe intensity domain. Fifteen active subjects (VO(2)max - 41.2 +/- 5.1 ml.kg(-1).min(-1)) performed the following tests: 1) an incremental test to determine the VO(2)max and the work rate associated with the VO(2)max (IVO(2)max) and; 2) two CWR transitions at 95% of the IVO(2)max to determine the slope of the VO2 slow component and the tlim. Three tlims were obtained: tlim1 = CWR1; tlim2 = CWR2; and tlim1+ 2 = (CWR1 + CWR2) / 2. There was no significant difference between the VO(2)max (3271.7 +/- 410.7 mL.min(-1)) and VO(2)peak obtained during the CWR tests (CWR1 = 3356.3 +/- 448.8 mL.min(-1), CWR2 = 3362.2 +/- 393.4 mL.min(-1), p > 0.05). Significant correlations (p < 0.05) were found among the VO(2)sc kinetics and tlim1 (r = -0.53), tlim2 (r = -0.49) and tlim1+2 (r = -0.55). Thus, exercise tolerance during CWR performed within the severe intensity domain is partially explained by the slope of the VO2 slow component.
Keywords: Exercise performance; Oxygen kinetics; Cycling; Endurance; Fatigue